Hubungan Perilaku Gaya Hidup dengan Kejadian Hipertensi pada Lansia - Isni Hijriana; Syamsuddin Syamsuddin; Nadia Syafira; Saiful Bahri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Hypertension is still a dangerous health problem in the elderly. The number of people with hypertension is increasing every year from 25.8% in 2013 to 34.1% in 2018, even increasing at the age of 50-69 years. Many factors that cause hypertension, one of which is a lifestyle factor that is not good. The purpose of this study was to analyze the relationship between lifestyle and the incidence of hypertension in the elderly in the working area of Ujong Rimba Public Health Center. This research is quantitative with a cross sectional approach. The population in this study were 102 people. Samples were taken using the Slovin formula as many as 50 people, with purposive sampling technique. Data analysis to analyze the relationship of lifestyle with the incidence of hypertension by using the chi-square test. The results showed that there was no relationship between physical activity and the incidence of hypertension, with p value = 0.497, there was a relationship between diet and the incidence of hypertension, with p value = 0.002, there was a relationship between resting habits and the incidence of hypertension, with p value = 0.007. This study recommends the elderly to always follow the recommendations of healthy living, control blood pressure, exercise regularly. It is hoped that health workers at the Health Center will improve health education about a good lifestyle to prevent hypertension.